Food management of early introduced caprine and bovine herds in the early Neolithic site of La Draga (Banyoles): An isotopic approach. (5th September 2019) - Navarrete, Vanessa; Tornero, Carlos; Balasse, Marie; Saña, Maria
Abstract: The arrival of early farmers and their livestock in the western Mediterranean during the early Neolithic marked a new way of life for the north‐east Iberian Peninsula. Given the permanence of the introduced economic strategies, which are still practiced today, and their apparently momentous outcome, this process has generally been explained as a success. The introduction of livestock must have played a fundamental role, but we know little about how these newly arrived domestic animals were managed. In this sense, the management of food habits of domestic animals could be a key factor to understand the success of different herding systems during the introduction and adaptation of domesticates in the Iberian Peninsula. Sequential analyses of δ 13 C and δ 18 O values in tooth enamel crowns are here used to provide detailed information about dietary inputs of early caprine and bovine herds introduced into the Iberian Peninsula. Our study was carried out at La Draga (5314–5209 cal BC), a site on the eastern side of Lake Banyoles (Girona, NE Iberian Peninsula). Data show that caprine and bovine herds were fed with variable foddering strategies. Sheep reflect feeding in the swamps or on forest resources with reduced seasonal dietary changes. Goat and cattle herds display food habits that could involve foddering on stored agricultural by‐products during specific season times, probably linked to reproductive and productive strategies. This information helps to reconstruct how these early Neolithic communities found the way to success in the new territories of the western Mediterranean.